Antologia Polskiej Animacji Eksperymentalnej - Borowczyk, Walerian; Lenica, Jan; Robakovski, Józef; Urbański, Kazimierz; Neumann, Hieronim (Polskie Wydawnictwo Audiowizualne, 2008)
Experimental animation is a broad notion that can be applied to many genres of animated film that break with formal and narrative conventions. The present anthology is a selection of some forty productions that do not quite fit into the mainstream of film animation. On the three discs the viewer will find abstract films, films composed of photographic images subjected to manipulation, as well as animations drawn in unconventional fashion. Some of these are works by well-known artists from beyond the cinematic milieu - writer Stefan Themerson and his painter wife Franciszka, for example, the designer Andrzej Pawłowski, or the photographer Tomek Sikora. There are also works by leading Polish contemporary artists like Józef Robakowski and Jerzy Kalina. There is no lack of work by world-renowned animators like Jan Lenica, Walerian Borowczyk, Zbigniew Rybczyński or Jerzy Kucia. The choice of films included in the Anthology of Polish Experimental Animation is so varied that every viewer is sure to find something of great interest. (Marcin Giżycki) [www.pwa.gov.pl]